Uwagi o historycznym charakterze antropologii ekologicznej - Kośmicki, Eugeniusz (Polskie Towarzystwo Antropologiczne, 1987)
The changes of ecology in the course of the history of human species permit to formulate an anthropological conception of a homeostasis being the regulator of the process of taking nature into possession.
Remarks about the historical character of ecological anthropology